Exploration of molecular features of PCOS with different androgen levels and immune-related prognostic biomarkers associated with implantation failure - Gao, Qinyu; Ma, Cong; Meng, Shuyu; Wang, Guanxiong; Xing, Qiong; Xu, Yuping; He, Xiaojin; Wang, Tianjuan; Cao, Yunxia (Frontiers in Endocrinology, 2022)
Background: Polycystic ovary syndrome (PCOS), the most common heterogeneous reproductive disease afflicting women of childbearing age, has been recognized as a chronic inflammatory disease recently. Most PCOS patients have hyperandrogenism, indicating a poor prognosis and poor pregnancy outcomes. The molecular mechanism underlying PCOS development is still unknown. In the present study, we investigated the gene expression profiling characteristics of PCOS with hyperandrogenism (HA) or without hyperandrogenism (NHA) and identified immune-related factors that correlated with embryo implantation failure. Methods: PCOS and recurrent implantation failure (RIF) microarray datasets were obtained from the Gene Expression Omnibus (GEO) database. ClueGO software was used to perform enrichment analysis of differentially expressed genes (DEGs) in PCOS with varying androgen levels. The Weighted Co-Expression Network Analysis (WGCNA) was used to identify co-expressed modules and shared gene signatures between HA PCOS and RIF. Moreover, the upregulated DEGs of HA PCOS and RIF were intersected with shared gene signatures screening by WGCNA to excavate further key prognostic biomarkers related to implantation failure of HA PCOS. The selected biomarker was verified by qRT-PCR. Results: A total of 271 DEGs were found in HA PCOS granulosa cell samples, and 720 DEGs were found in NHA PCOS. According to CuleGO enrichment analysis, DEGs in HA PCOS are enriched in immune activation and inflammatory response. In contrast, DEGs in NHA PCOS are enriched in mesenchymal cell development and extracellular space. Using WGCNA analysis, we discovered 26 shared gene signatures between HA PCOS and RIF, which were involved in corticosteroid metabolism, bone maturation and immune regulation. DAPK2 was furtherly screened out and verified to be closely related with the development of HA PCOS, acting as an independent predictor biomarker of the embryo implantation failure. DAPK2 expression was negatively correlated to the embryo implantation rate (r=-0.474, P=0.003). The immune infiltration results suggested that upregulated DAPK2 expression was closely related with NK cell infiltration and macrophage M2, playing an essential role in the pathogenesis of implantation failure in HA PCOS. Conclusion: Our research revealed the expression profiling of PCOS with different androgen levels and identified DAPK2 as a critical prognostic biomarker for implantation failure in PCOS.